Changes in pupillometry associated with dissipated energy during phacoemulsification. Issue 6 (November 2021) - Coco, Giulia; Cremonesi, Pierluca; Menassa, Nardine; Pagano, Luca; Gadhvi, Kunal A; Semeraro, Francesco; Kaye, Stephen B; Romano, Vito
Purpose: To investigate the effect of ultrasound level during phacoemulsification on pupil dynamics. Methods: Comparative retrospective study on patients who underwent routine cataract surgery at the Royal Liverpool University Hospital. Clinical parameters, anterior chamber measurements, axial length, surgeon grade, time of surgery, level of ultrasound used (cumulative dissipated energy, CDE), intra- and post-operative complications were collected. Pupil diameters were collected before and 4 ± 1 weeks after surgery in static scotopic, mesopic, photopic pupil conditions. Also, pupil dynamic measurements after luminous stimulus were recorded. Changes in static pupil diameters, relative dilation at 3.5 s after luminous stimulus, and time to reach 75% and 95% of maximum dilation were measured. Results: Forty-eight eyes of 24 patients (13 males) were included with a mean age of 73.1 ± 14.6 years. Mean CDE value was 18.11 ± 10.56. Mean scotopic pupil diameters decreased by 0.24 ± 0.48 mm ( p  = 0.021) in the operated eye. Significant correlation was found between reduction in scotopic pupil diameter and CDE ( p  = 0.05). A generalized linear model confirmed that the level of CDE was significantly associated with reduction in scotopic pupil diameter ( p  = 0.026). Patients who underwent surgeries with lower CDE (0 < CDE ⩽ 10 and 10 < CDE ⩽ 20) did not experience significant changes in scotopic pupil diameter after surgery ( p  = 0.28 and p  = 0.79, respectively) as opposed to those with higher CDE (CDE > 20; p  = 0.03). Conclusion: Phacoemulsification cataract surgery and the cumulative dissipated energy may be associated with changes in pupil behaviour.